Cultura escolar e cultura da escola : produção e reprodução - Demenech, Flaviana (2015)
The teaching of the universal process has lived different times in Brazilian education, driven by popular media and organized by the economic context in constant transformation. Considering the criticisms that are made to the school institution by authors such as P. Bourdieu, J-C. Passeron and L. Althusser, this paper aims to investigate the tensions, old and new contradictions are (re) produced in the public school as the heterogeneity through the presence of subjects (children, youth, parents, programs, professionals from other areas) who bring different characteristics of the planned - languages, actions, customs - enters school and remains in it, clashing with the impregnated homogeneity in its design cultural, historically constructed. Therefore, it seeks on the contributions of B. Lahire, J. Ezpeleta and E. Rockwell understanding of school culture, school culture, the arrangements, of recorded history and undocumented, produced daily in schools and which make each school to constitute itself distinguished the other or resembling each other. The analysis was upheld by the integration of the data described and concepts selected by elected theoretical approaches, in particular the reproduction of categories, habitus, provisions, everyday school life and contradiction. In terms of methodological procedures two ethnographic case studies were performed, bringing together elements of everyday life for two schools in suburbs of Passo Fundo. The results of the analysis of the data produced are exposed in the two topics: on the one hand, interschool factors that characterize and constitute the way about the tensions arising from the interaction with heterogeneous, described by the categories: Home; Speech about the place and the school function; Centralized authority versus collegiate management; and, on the other, the extraschool factors, which show the school's relations with the external environment to him and going through the experience of these tensions, described by the categories: Relation family / school; Educational and social policies. It was concluded, that there is an investment of both schools at the student's presence the home, in school management, personal investment management team, for the student to remain at school, building in the process of school identity. However, although each school has its identity, school culture, which is created from its context and its demand, nevertheless, school culture is present, holding up institutionally, producing and reproducing tensions, old and new contradictions